ADAPTASI ALAT UKUR KOMITMEN KARIER - Ingarianti, Tri Muji; Fajrianthi, Fajrianthi; Purwono, Urip (Jurnal Psikologi, 2019)
Career commitment is a motivation, attitude, and behavior shown by individuals in a profession to live and survive in the chosen career role. Career commitment has three dimensions, namely career identity (career identity), career planning, and career resilience. Career Commitment Measure (CCM) is an instrument measuring career commitment which has been used widely across countries. To use the instrument in different culture, the adaptation process is necessary so that the adapted instrument becomes valid and reliable. However, there is still little detailed information related to research that focuses on developing career commitment measurement tools, especially in Indonesia. The purpose of this study was to obtain a standardized version of Indonesia's career commitment measurement tool. The International Test Commission (2016) guideline was used in the process of adaptation. Based on the results of the CFA analysis using the AMOS 22 program, it can be concluded that the overall career commitment model with indicators consisting of three dimensions, namely career planning, career identity and career resilience, has a good fit model. The null hypothesis means that the career commitment model of goodness of fit is acceptable. This explains that the resulting model can describe the actual conditions.